2008
DOI: 10.1128/jb.00512-08
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of Vibrio cholerae ToxT in Transcription Activation of Genes Having Altered Promoter Spacing

Abstract: Cholera, a severe diarrheal disease, is caused by ingestion of the gram-negative bacterium Vibrio cholerae. Expression of V. cholerae virulence factors is highly regulated at the transcriptional and posttranscriptional levels by a complex network of proteins and small noncoding RNAs. The direct activator of transcription of most V. cholerae virulence genes is the ToxT protein. ToxT binds to a 13-bp sequence, the toxbox, located upstream of genes in its regulon. However, the organization of toxboxes relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The DNA sequences of the identified toxboxes are consistent with the consensus toxbox in that they are degenerate but contain the 5= poly(T) tracts common among all known ToxT DNA binding sites (42)(43)(44). The toxboxes in PctxAB are also consistent with other ToxT-activated promoters in their positioning relative to the transcriptional start site (2,(42)(43)(44). Although ToxT is a flexible transcription activator in regard to sequence requirements, configuration, and the number of binding sites, it has specific requirements for the activation of PctxAB, and a single mutation within one the two toxboxes is enough to severely decrease transcription activation by ToxT.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The DNA sequences of the identified toxboxes are consistent with the consensus toxbox in that they are degenerate but contain the 5= poly(T) tracts common among all known ToxT DNA binding sites (42)(43)(44). The toxboxes in PctxAB are also consistent with other ToxT-activated promoters in their positioning relative to the transcriptional start site (2,(42)(43)(44). Although ToxT is a flexible transcription activator in regard to sequence requirements, configuration, and the number of binding sites, it has specific requirements for the activation of PctxAB, and a single mutation within one the two toxboxes is enough to severely decrease transcription activation by ToxT.…”
Section: Discussionsupporting
confidence: 55%
“…Individual point mutations within a region spanning positions Ϫ72 to Ϫ59 caused severe defects in ToxTdependent activity, with the exception of positions Ϫ65 and Ϫ64. This 13-bp sequence, which we designated toxbox 1, is consistent with previously characterized ToxT binding sites in both sequence and proximity to the transcriptional start site (2,(42)(43)(44). Interestingly, there are no single point mutations within toxbox 1 that significantly increased ToxT-independent activity, unlike the double point mutation within heptad repeat 5.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…ToxT is thought to have optimal activity when acting as a dimer (27)(28)(29)(30)(31). In contrast, it also has been shown that ToxT can bind DNA as a monomer (18,19,26). The sigmoidal ToxT binding curve at two toxbox promoters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All ToxT-dependent virulence genes have two toxboxes upstream of their transcriptional start site in either direct or inverted repeat configurations, with the exception of aldA, which has only a single toxbox (19). ToxT can bind toxboxes as a monomer (18,19,26) but is presumed to dimerize to fully activate at least some virulence genes (27)(28)(29)(30)(31). The activation of the ToxT-dependent virulence genes can be altered in the presence of the positive and negative ToxT effectors.…”
mentioning
confidence: 99%